Use of Social Media by the Undergraduate Medical Students: Students’ Perception in Selected Medical Colleges of Bangladesh (Bangladesh Journal of Medical Education, 2018)
Introduction: This descriptive type of cross sectional study was carried out to explore the extent of use of social media by the undergraduate medical students and its consequences in medical education. This study was carried out in nine (Four public and five private) medical colleges all over Bangladesh during a period from July 2016-2017.Objective: The study revealed that the use of social media by the undergraduate medical students and its effect on their lifestyle and medical education.Methodology: Sample size was 673 medical students. Data was collected by self-administered semi-structured questionnaire from 673 respondents. Convenience sampling technique was adopted for data collection. For each variable frequency and percentages was calculated. There was also a part of in-depth interview for the respondents on the perception of use of Social media.Results: Among the students 54.68% females & 45.34% males, the mean age of the respondents was 20.76 years. Around 42.6% respondents were using Social media for4-6 years. The main use of social media by the respondents was Facebook 70.1%, main devices was mobile phone 96.8%. The main purpose of using the Social media for non-academic purposes such as, communicate with others26.0%, for chatting 51.3%. Maxium duration > 4 times / day up to >6 hours. Academic purpose 44.7% users using the SM every day. Six hundred forty six respondents agreed for negative effect of social media. 52.2% agreed that they used Social media during lecture class.Conclusion: Most students had positive thoughts towards using social media. Students were using social media for almost nonprofessional reason. So, there is need to build up widespread awareness to use social media by medical students for professionalisms.Bangladesh Journal of Medical Education Vol.9(2) 2018: 11-15